Contraceptive methods adopted by women in immediate post-partum period in a tertiary care centre in Northern India: an observational study - Saurabh, Suvidha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Contraception is the need of the hour in India. The family planning program in India offers a basket of choices. These choices are governed by the decisions of their partners, socio economic status of patients and even wishes of other family members. Methods: This observational study was carried out in obstetrics and gynaecology department of ESIC medical college and hospital for a period of 1 year from March 2023 to February 2024. All the patients who were in immediate post-partum period after normal vaginal delivery, caesarean section and medical termination of pregnancy were included in the study. Results: With the introduction of PPIUCD in national family programs more women are inclining towards long term spacing methods and not resorting to permanent sterilisation alone. Conclusions: It is undeniable that most women do not desire a pregnancy immediately after delivery but are not informed enough about the methods of contraception they can use.